The Influence of Hen Aging on Eggshell Ultrastructure and Shell Mineral Components - Park, Ji-Ae (Korean J Food Sci Anim Resour, 2018)
The eggshell, which is a complex and highly ordered structure, is very important factor for food safety and egg marketing. This study investigated the changes in eggshell structure and shell components in relationship to hen age. For this study, we examined the histological change of the endometrium of the 30-, 60-, and 72-wk-old commercial layers, and analyzed the ultrastructure and ionic composition of their eggshells. The results showed that histological deformation, fibrosis, atrophy and elimination of micro-villi in the uterus endometrium were found through microscopic observation that was associated with increasing hen age. Concentration of blood-ion components such as Ca(2+), Na(+), K(+), and Cl(–) ions did not change with age. Along with the results from the ultrastructure analysis of the eggshell, the palisade layer ratio and the density of mammillary knobs were significantly decreased in older hens. In addition, the type B mammillary knobs were frequently observed with increasing hen age. In the mineral element assay from the eggshell, Ca(2+), S(2–), and Co(2+) significantly decreased with increasing hen age, whereas Na(+), K(+), and V(2+) significantly increased. Therefore, the damages of endometrial tissue inhibit the processes of ion transmission and the crystallization of eggshell formation, resulting in a large and non-uniform mammillary knob formation. This means the conditions of endometrial cells affect the formation of the eggshell structure. In conclusion, hen aging causes the weakness of the eggshell and degrades the eggshell quality.